THE INFLUENCE OF LEGAL COMPLIANCE OF HUMAN RESOURCE POLICIES AND THE IMPLEMENTATION OF CORPORATE GOVERNANCE ON EMPLOYEE PERFORMANCE: THE ROLE OF JOB SATISFACTION AND K3 LEGAL ASSURANCE AS MEDIATION VARIABLES (A Study of PT. Trio Kencana, Parigi Mouton - M.Amsyahar; Alamsyah; Nur Indah; Astri Aryanti Amsyahar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze and prove the influence of legal compliance of human resource policies and the implementation of good corporate governance on employee performance, as well as to test the role of job satisfaction and legal guarantees of Occupational Safety and Health (K3) as mediating variables. The background of the study is based on the phenomenon of the continued inconsistency of internal policy implementation with laws and regulations, as well as the weak application of governance principles which result in performance fluctuations and the risk of legal disputes in mining companies. This study was conducted at PT. Trio Kencana, a large-scale gold mining company operating in Parigi Moutong Regency, Central Sulawesi, with a total of 500 permanent employees as respondents. The research method uses a quantitative approach with an explanatory research design. The data analysis techniques used are descriptive analysis, classical assumption tests, multiple linear regression analysis, and path analysis with the help of IBM SPSS Statistics 25 software. The results of the study prove that: (1) Legal compliance of human resource policies and the implementation of corporate governance have a positive and significant effect on job satisfaction and legal guarantees of K3; (2) Legal compliance of human resource policies and the implementation of corporate governance have a positive and significant effect on employee performance; (3) Job satisfaction and legal assurance of OHS have a positive and significant effect on employee performance; and (4) Job satisfaction and legal assurance of OHS have been proven to be able to partially and significantly mediate the effect of legal compliance of human resource policies and the implementation of corporate governance on employee performance. These findings confirm that the legal aspect is not merely a formality, but rather a strategic business instrument. This study concludes that improving employee performance and business sustainability can only be achieved if the company aligns all management policies with applicable legal provisions, implements transparent governance, and guarantees legal certainty for employee safety and welfare. The results of this study provide theoretical contributions to the development of business and management law, as well as practical recommendations for mining company management in designing policies based on legal compliance and labor protection.